2004
DOI: 10.1021/nl048715d
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Cellular Toxicity of Nanocrystal Quantum Dots Depend on Their Surface Modification

Abstract: Nanocrystal quantum dots (QDs) have been applied to molecular biology because of their greater and longer fluorescence. Here we report the potential cytotoxicity of our characterized QDs modified with various molecules. Surface modification of QDs changed their physicochemical properties. In addition, the cytotoxicity of QDs was dependent on their surface molecules. These results suggested that the properties of QDs are not related to those of QD-core materials but to molecules covering the surface of QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
622
2
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 918 publications
(653 citation statements)
references
References 32 publications
19
622
2
5
Order By: Relevance
“…In spite of the large number of studies aimed at establishing the biological activity of nanoparticles and the influence of important physico-chemical parameters such as size, surface properties, crystal phase and others (Hoshino et al 2004;Magrez et al 2006;Oberdorster et al 2005b); the use of appropriate dose metrics needs to be carefully considered. For example, to determine the effect of size of the nanoparticle on biological activity, should comparisons of activity or biological response be based on the mass of the sample, as is done in conventional toxicological studies, or should the metric be total surface area when comparing effects of different sized particles?…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the large number of studies aimed at establishing the biological activity of nanoparticles and the influence of important physico-chemical parameters such as size, surface properties, crystal phase and others (Hoshino et al 2004;Magrez et al 2006;Oberdorster et al 2005b); the use of appropriate dose metrics needs to be carefully considered. For example, to determine the effect of size of the nanoparticle on biological activity, should comparisons of activity or biological response be based on the mass of the sample, as is done in conventional toxicological studies, or should the metric be total surface area when comparing effects of different sized particles?…”
Section: Introductionmentioning
confidence: 99%
“…Surface derivatization and light exposure are known to greatly affect the toxicity of semiconductor nanoparticles (20,69,70), TiO2 nanoparticles (71,72), and fullerenes (45,48,(73)(74)(75)(76). Many believe that surface coatings have the potential to greatly alter the toxicity, solubility, reactivity, bioavailability, and catalytic properties of underlying nanoparticles, thus minimizing their health and environmental impacts.…”
Section: Research Outcomes and The Risks Of Nanotechnologymentioning
confidence: 99%
“…In the event that the surface coating does not persist, CdSe (like CdTe and CdS) is known to be toxic in bulk form and may be particularly reactive and bioavailable in nanoparticulate form. Meanwhile, watersoluble CdSe quantum dots without surface coatings can cause DNA damage (78) and can be toxic to cells (20,69,70,79), although the mechanism for toxicity is still being debated in the literature.…”
Section: Research Outcomes and The Risks Of Nanotechnologymentioning
confidence: 99%
“…Most of the above cell and animal experiments showed that when properly capped by both ZnS and hydrophilic shells, no obvious CdSe nanocrystal toxicity was observed under normal experimental conditions. Several groups have varied parameters such as synthesis, surface coating and incubation concentration to further investigate the potential toxicities of nanocrystals [24,[43][44][45]. Cytotoxicity was observed when Cd 2+ or Se 2+ ions were released.…”
Section: Toxicitymentioning
confidence: 99%